ANALYSIS OF TRANSPORT MARKET IN SLOVAK REPUBLIC - Ondrus, Jan; Dicova, Jana (Doprava a spoje, 2010)
Competitive environment and market internationalisation offers to transport new opportunities, where transport enterprises have possibility to apply entrepreneurially idea, strengthen to actual competitiveness and obtain to advantageous position on market. The paper deals with assess of actual possibilities of development transport market, as place of orientation all entrepreneurially activities, with application of new trend in transport management and development of transport.